Changing Library Reader’s Services in Nigeria Universities: New Reality from Covid-19 Pandemic - Abdulrazaq Olanrewaju Mutalib; Jamiu Wankasi Abdulraheem; Najeebat Opeyemi Abdulraheem; Olabisi Grace Babafemi (Indonesian Journal of Librarianship, 2025)
Background/Problem Statement: The COVID-19 pandemic disrupted university library operations in Nigeria, significantly limiting physical access to library services and creating challenges for students, lecturers, and researchers in obtaining timely information. The sudden shift to remote and digital services exposed gaps in infrastructure, professional skills, and preparedness, especially in developing countries where technological adoption is slower. Consequently, there was a need to assess how university libraries and librarians adapted their reader services during the pandemic to meet users' evolving information needs. . Purpose:    This study examines change in readers’ services in Nigeria universities: new reality from COVID- 19 pandemic Method:  The study adopts qualitative research method. The purposive sampling technique was adopted for the study as the participants were sampled on the ground of being professional librarians in university of Ilorin library. The total number of participant was seven. The structured interview was used to collect data on the convenient time of the participants. Thematic analysis was used to analyze the final version of the interview transcript. Result:  Interviews with professional librarians supported these findings, revealing that university libraries adopted various innovations such as subscription to electronic resources, development of library guides, and increased use of library websites to continue serving users . The majority of library services during the pandemic were delivered through electronic formats, highlighting a shift towards digital engagement. Conclusion:    The finding of the study revealed that majority of participants noted the services by professional librarians during COVID 19 to users were through electronic formats. The study recommends that training and workshop should be organized for library users and library professional on the use of current information tools. Keywords: Service Quality, Perception, Exclusive Library